A fluorescent activatable probe for imaging intracellular Mg2+ 1. Issue 2 (19th December 2017) - Treadwell, Ryan; de Moliner, Fabio; Subiros-Funosas, Ramon; Hurd, Toby; Knox, Kirsten; Vendrell, Marc
Abstract : An BODIPY probe for detection and imaging of Mg 2+ without interference from Ca 2+ is described. Abstract : An activatable BODIPY probe for in vitro detection and fluorescence cell imaging of free Mg 2+ without interference from Ca 2+ is described. Fluorescence amplification of the probe is observed upon detection of physiological concentrations of Mg 2+ due to reduced rotation of the fluorophore and effective chelation by a quinolizine-based core.